2023
DOI: 10.1038/s41467-023-37477-x
|View full text |Cite
|
Sign up to set email alerts
|

Explainable multi-task learning for multi-modality biological data analysis

Abstract: Current biotechnologies can simultaneously measure multiple high-dimensional modalities (e.g., RNA, DNA accessibility, and protein) from the same cells. A combination of different analytical tasks (e.g., multi-modal integration and cross-modal analysis) is required to comprehensively understand such data, inferring how gene regulation drives biological diversity and functions. However, current analytical methods are designed to perform a single task, only providing a partial picture of the multi-modal data. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…This suggests that some groups of cells exhibited consistent e-features among the cell types. The heterogeneity of the e-features can be associated with the finer subtypes of each cell type 8 . Moreover, we discovered that both excitatory and inhibitory cell types were included in the same cluster, consistent with the findings from a previous study 11 ; for these cell types, we observed continuous changes in the e-features of glutamatergic and GABAergic neurons in the primary motor cortex of mice.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that some groups of cells exhibited consistent e-features among the cell types. The heterogeneity of the e-features can be associated with the finer subtypes of each cell type 8 . Moreover, we discovered that both excitatory and inhibitory cell types were included in the same cluster, consistent with the findings from a previous study 11 ; for these cell types, we observed continuous changes in the e-features of glutamatergic and GABAergic neurons in the primary motor cortex of mice.…”
Section: Resultsmentioning
confidence: 99%
“…By integrating and analyzing multi-omic data, including transcriptomics, single-cell, and genomics, we can dissect the underlying gene regulatory mechanisms and unveil the landscape of the tumor microenvironment. This deepens our understanding of the interactions and biological mechanisms between immune and tumor cells [31,32]. However, the complexity and growing volume of multi-omics data introduce new opportunities and challenges in analyzing the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Contextualising affinities among latent representation learning with other pivotal tasks in single-cell analysis like GRN inference, cell clustering, multi-modal inference could be a viable way to allow DL architectures to capture better the systemic changes that a perturbation can confer across diverse cell populations. Recent tools like UnitedNet [83] , adopted in a perturbational landscape, could be highly informative for better future inferences of multi-modal Perturb-seq models.…”
Section: Discussionmentioning
confidence: 99%